New strategies for targeting drug combinations to overcome mutation-driven drug resistance. (February 2017) - Wang, Linyan; Wang, Haiyun; Song, Dongli; Xu, Menglin; Liebmen, Michael
Abstract: Targeted therapies are suggested as an effective alternative for patients with cancer that harbor mutations, but treatment outcomes are frequently limited by primary or acquired drug resistance. The present review describes potential mechanisms of primary or acquired drug resistances to provide a resource for considering how to be overcome. We focus on strategies of targeted drug combinations to minimize the development of drug resistance within the context how resistance develops. Strategies benefit from the combined use of "omics" technologies, i.e., high-throughput functional genomics data, pharmacogenomics, or genome-wide CRISPR-Cas9 screening, to analyze and design targeted drug combinations for mutation-driven drug resistance. We also introduce new insights towards pathway-centric combined therapies as an alternative to overcome the heterogeneity and benefit patient prognoses.